Smart Library Automation: Integrating Classification Tree-Based cataloging with XAMPP Server Environment - Teneke, Nora Godwin; Etemi, Joshua Garba; Kamak, Yamlach Shedrack; Ariwa, Rosemary Ngozi (ABUAD Journal of Engineering Research and Development, 2024)
Various sectors, including libraries, have experienced a revolution due to the swift progress of technology. This involves introducing automation and monitoring systems for more efficient operations. Hence the study Smart Library Automation and Monitoring System as an appropriate solution for these technological advancements. The proposed system integrates cutting-edge technologies to create a smart interconnected library ecosystem. Object Oriented Design Methodology was used as the software engineering technique, the proposed system leverages classification tree-based cataloging, a hierarchical organization method that enhances the accessibility and navigability of library collections. JavaScript, PHP, HTML, CSS, and XML technologies are integrated to develop an intuitive and interactive user interface for the library management system, XAMMP was later used as local server environment to utilize the automation. The system boasts various advanced functions, such as automatic lending and returning of books, shelf monitoring, and cataloging for resource accessibility assurance. By integrating these features into a comprehensive library management solution, it enables proficient utilization with intellectuality sustainability on par with the modern digital era standards.